Asian Financial Crisis: Overview of Asian Crisis and Recovery Progress - Noerlina, Noerlina; Dewi, Sylvia Cinthya (Journal the Winners: Economics, Business, Management, and Information System Journal, 2003)
The rapid recovery in Asia economies in some ways of a surprise because many countries in Asia had tried a lot of ways to stabilize the economy from the crisis’ pressure in 1997. As a result, most of these countries in Asia slowly recover by the step of restructuring in the financial sector, such as fiscal adjustment and the continuation of a floating exchange rate system.